Reimagining apocalypticism : apocalyptic literature in the dead sea scrolls and related writings - DiTommaso, Lorenzo; Goff, Matthew J. (SBL Press, 2023)
The Dead Sea Scrolls have expanded the corpus of early Jewish apocalyptic literature and tested scholars' ideas of what apocalyptic means. With all the scrolls now available for study, contributors to this volume engage those texts and many more to reexplore not only definitions of the genre but also the influence of the Dead Sea Scrolls on the study of apocalyptic literature in the Second Temple period and beyond. Part 1 focuses on debates about categories and genre. Part 2 explores ancient Jewish texts from the Second Temple period to the early rabbinic era. Part 3 brings the results of scroll research into dialogue with the New Testament and early Christian writings. -- Provided by publisher
Keywords: Dead Sea scrolls.; Dead Sea scrolls -- Criticism and interpretation.; Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish.; Bible. -- Ancien Testament -- Critique, interprétation, etc. juives.; Bible. -- Old Testament; Dead Sea scrolls; Apocalyptic literature -- History and criticism.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Eschatology, Jewish -- History.; Eschatology -- History of doctrines -- Early church, ca. 30-600.; Littérature apocalyptique -- Histoire et critique.; Judaïsme -- Histoire -- 586 av. J.-C.-210 (Période postexilique); Eschatologie juive -- Histoire.; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Apocalyptic literature; Criticism, interpretation, etc.